Wellbeing for young elite musicians: development of a health protocol from a student perspective - Ann Shoebridge; Margaret S. Osborne; Margaret S. Osborne (Frontiers in Psychology)
Musicians’ vulnerability to psychological and physical problems provides a compelling argument to include health and wellbeing training in music education. This study forms part of a larger project to design an evidence-based wellbeing protocol for young elite musicians at a pre-professional music training institute. Recommendations from the health, education, performance science, behavior change, and occupational and public health literature provided theoretical and practical foundations for the project. The aim of this study was to identify barriers to wellbeing and strengths of an existing health protocol, and provide recommendations for change from the student perspective. Four in-person focus groups were held on the same day, attended by 68% (n = 45) of the student cohort. Semi-structured discussions were recorded, transcribed and analyzed thematically. Barriers to wellbeing and recommendations for change were collated from the data and distributed to the student body to be rated in priority order. Participants appreciated the existing program for its holistic approach delivered by a range of skilled practitioners. Barriers to wellbeing included constraints in finances, leave allowances and time, pressure from interpersonal challenges and unhealthy norms in the music performance culture. Recommendations for change included updating the financial policy; having more flexible leave conditions to allow higher earnings and better access to performance opportunities; having reliably scheduled time off; collaborative planning with staff around playing rosters; more activities for musician enhancement and social bonding; exercise opportunities in-house; addressing pervasive cultural norms around practice and breaks; education regarding respectful and professional conduct; an effective complaints procedure, and more practical wellbeing sessions.